Self-talk for weight loss lose weight, keep it off, and never diet again - Helmstetter, Shad (St. Martin's Paperbacks, 1996)
A guide to the self-talk method of weight loss explains that overeating is a symptom of mental ""programming"" that results in poor dietary habits and presents exercises in setting realistic goals, building self-esteem, and becoming naturally thin. Reprint.